2010
DOI: 10.2165/10482880-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib

Abstract: Erlotinib (Tarceva), an oral epidermal growth factor receptor tyrosine kinase inhibitor, is associated with modest improvements in survival in patients with advanced non-small cell lung cancer (NSCLC) who have previously received one or more prior chemotherapy regimens. In a well designed clinical trial in this patient population, median overall survival and progression-free survival were significantly longer in patients receiving erlotinib 150 mg/day than in those receiving placebo. Erlotinib is generally wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…DTX, a microtubule-stabilizing taxane, is used in clinic for the treatment of metastatic breast cancer 27,28 . Along with its potent anticancer activity, DTX also exhibits serious doselimiting toxicities partly due to the formulation excipients.…”
Section: Resultsmentioning
confidence: 99%
“…DTX, a microtubule-stabilizing taxane, is used in clinic for the treatment of metastatic breast cancer 27,28 . Along with its potent anticancer activity, DTX also exhibits serious doselimiting toxicities partly due to the formulation excipients.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, if a drug can inhibit EGFR, and also be activated under carcinoma hypoxia, it may exert a stronger effect. Recently, many small molecule EGFR inhibitors have been successfully developed and introduced onto the market, these drugs include gefitinib ( 1 ),9 erlotinib ( 2 ),10 lapatinib ( 3 ),11 osimertinib ( 4 ),12 etc (Figure 1). In addition, reagents targeting carcinoma-hypoxia have been massively explored, including the 2-nitroimidazole derivative pimonidazole ( 5 ),13 nimorazole ( 6 ),14 and so on (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Previous cost comparisons (including a review) published prior to loss of patent for docetaxel, showed that erlotinib was less costly than docetaxel, which in turn was less costly than pemetrexed, across different health care settings and different years of publication 2632…”
Section: Introductionmentioning
confidence: 99%